High quality hybrid perovskite semiconductor thin films with remarkably enhanced luminescence and defect suppression via quaternary alkyl ammonium salt based treatment - Naphade, Rounak A.; Zhao, Baodan; Richter, Johannes M.; Booker, Edward; Krishnamurthy, Shrreya; Friend, Richard H.; Sadhanala, Aditya; Ogale, Satishchandra B. (Advanced Materials Interfaces, 2017)
Significant enhancement in the luminescence and superior photophysical properties of CH3NH3PbBr3 thin films prepared via simple single step spin coating process involving a novel additive mediated solvent extraction step is reported. This process results in significantly lower disorder in CH3NH3PbBr3 perovskites with Urbach energies reducing from ≈35 to ≈17 meV, which is the lowest reported value to date. The additive mediated process also results in a remarkable improvement in the photoluminescence quantum yields (PLQYs) from 1% to 30%. Coupled with the overall increase in surface roughness, a significant increase in the internal PLQY from 7% to 77% is estimated, indicating the superior quality of the treated thin films. The resultant high quality CH3NH3PbBr3 perovskites with remarkable photophysical properties can be used in realizing highly efficient optoelectronic devices. Highly efficient light emitting diodes using these perovskites are demonstrated here.